If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+5(-2x-3)=-3
We move all terms to the left:
7x+5(-2x-3)-(-3)=0
We add all the numbers together, and all the variables
7x+5(-2x-3)+3=0
We multiply parentheses
7x-10x-15+3=0
We add all the numbers together, and all the variables
-3x-12=0
We move all terms containing x to the left, all other terms to the right
-3x=12
x=12/-3
x=-4
| 1/4m^2+2m-5=0 | | -3z–8z=33 | | 6(2x-4)+2x=46 | | 10x-6x+193=10x+108 | | 30=-5(1+t) | | 1/4m^2-5=0 | | 200+2x^2=40x | | (7x-3)+(2x-6)=180 | | 13=6x−8 | | 10=-6w+4(w+3) | | 4=-d/2 | | 7=7-4x | | x-5(-4)=8 | | 20+3z=53 | | 12x+18=−18 | | 4=t/5+6 | | 2(2x+5)-x=-26 | | -7-5y=8 | | -6+2k=k | | 3y=4–7 | | 14=-8v+3(v-2) | | 6=9+p/3 | | -6(8+4n)=2(1-7n) | | 25+x/10=24 | | 4(3+y)=6+3(y+2) | | 25x^+9=0 | | -8=w/2-4 | | 2b+10(b-3)=3(b+2)+2b | | A=9+4b | | 8x-40+4x=44 | | X+(x+1)^2=109 | | -2(x-6)=3(x-4)-x |